2019
DOI: 10.3390/su11195250
|View full text |Cite
|
Sign up to set email alerts
|

Research Series Review for Transdisciplinarity Assessment—Validation with Sustainable Consumption and Production Research

Abstract: In light of the escalating challenges for the sustainability of our societies, the need for improving the research of sustainable consumption and production (SCP) aiming to make real changes on the societies towards sustainability is evident. Transdisciplinary (TD) research is a promising way to enhance SCP research; however, insights to operationalize the concept of TD research are needed for both funders and researchers. Therefore, this article proposes an innovative way to capture and analyse a research ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…An issue with the general quality of review articles, in general, is not new [54]. However, this issue deserves more attention now, as we face an "insanely" growing number of review articles (e.g., as reported in [55] (annual publications for systematic reviews in PubMed between 1991 and 2014 increased by 28 times, and many of them were concluded not to be useful)), but we are expected to conduct academic research for societal challenges in the real world [56] (often called trans-disciplinary research [23]): the recipients of the insights in an academic article are not only academic researchers in the concerned discipline, but also researchers in other disciplines and, more importantly, practitioners in industry and governments. For instance, in health research, a need was recently found to synthesize many review articles in a manner that is accessible and usable to practice [57].…”
Section: Systematic Literature Review and Literature Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…An issue with the general quality of review articles, in general, is not new [54]. However, this issue deserves more attention now, as we face an "insanely" growing number of review articles (e.g., as reported in [55] (annual publications for systematic reviews in PubMed between 1991 and 2014 increased by 28 times, and many of them were concluded not to be useful)), but we are expected to conduct academic research for societal challenges in the real world [56] (often called trans-disciplinary research [23]): the recipients of the insights in an academic article are not only academic researchers in the concerned discipline, but also researchers in other disciplines and, more importantly, practitioners in industry and governments. For instance, in health research, a need was recently found to synthesize many review articles in a manner that is accessible and usable to practice [57].…”
Section: Systematic Literature Review and Literature Synthesismentioning
confidence: 99%
“…Here, the evidence from industrial cases was considered, because the applicability and effects of BDA depend highly on contexts. This criterion originated from the target recipients, including practitioners in industry in the spirit of trans-disciplinary research series [56]. In addition, the aspects of contribution to design by each article were documented: quality, cost, time, and environment.…”
Section: Systematic Literature Review and Inter-disciplinary Meta Synmentioning
confidence: 99%
“…The relevance of co-creation in PSS design is confirmed with the practical case of Rolls-Royce (Smith, 2013) 1 . In general, this implies the importance of addressing the contexts in the industry practice, where the PSS design is performed (Sakao, 2019). The design object model for PSS by Maussang et al (2009) and the PSS design process model by Morelli (2003) consider the social construct and incorporate interaction between different actors, such as customers and a provider.…”
Section: Characteristics Of Pss Design and Previous Researchmentioning
confidence: 99%
“…The relevance of co-creation in PSS design is confirmed with the practical case of Rolls-Royce (Smith, 2013) 1 . In general, this implies the importance of addressing the contexts in the industry practice, where the PSS design is performed (Sakao, 2019).…”
Section: Research Motivation Based On the Literature Analysismentioning
confidence: 99%
“…Vergragt et al (2014) introduced four research frameworks, 11 enabling mechanisms, and nine main research areas, whereas Vergragt et al (2016) introduced ten different themes for SCP from 40 selected papers. Sakao (2019) proposed a model to review such SCP studies for transdisciplinary assessment. In addition, the literature has suggested that SCP policies have several aspects.…”
Section: The Academic Scpmentioning
confidence: 99%